MODEL DINAMIK PENILAIAN KESESUAIAN AGROKLIMAT TANAMAN KEDELAI(DYNAMIC MODEL OF AGROCLIMATIC SUITABILITY OF SOYBEAN) - H. Supriyadi; Y. Koesmaryono; L.H. Sibuea (Agromet, 2007)
The experiment aims to arrange of data-based of agroclimatic suitability for soybean, to arrange dynamic models for evaluation of suitability for soybean, and to evaluate agroclimatic suitability for soybean on computer. Secondary data of soybean yield and climate were collected from four locations of West Java as specific site targets, those were: Pusakanagara Subang, Cimanggu Bogor, Karangpawitan Garut, and Pasirsarongge Cianjur. Dynamic model has been developed as a tool to assess agroclimatic suitability of soybean which comprises the class, sub class, and sub-sub class level. The model provides information on land productivity, climatic constraint, stages of plant development that related to climate condition. Agroclimatic suitability is classified to five classes, i.e. S1 (very suitable), S2 (suitable), S3 (moderately suitable), S4 (not suitable), and S5 (very not suitable). Base on climate data of 2002, the models indicated that class of S1 were not found. While Cimanggu Bogor is classified as S2; Pusakanagara Subang and Karangpawitan Garut are classified as S3; and Pasirsarongge Cianjur is classified as S4.